Sampling techniques - Cochran,William G. (New Delhi: Willy Eastern Limited, 1977)
As did the previous editions, this textbooks presents a comprehensive account of sampling theory as it has been developed for use in sample surveys. It contains illustrations to show how the theory is applied in practice, and exercises to be worked by the student. The book will be useful both as a text for a course on sample surveys in which the major emphasis is on theory and for individual reading by the student.
Introduction -- Simple random sampling -- Sampling proportions and percentages -- The estimation of sample size -- Stratified random sampling -- Further aspects of stratified sampling -- Ratio estimators -- Regression estimators -- Systematic sampling -- Single-stage cluster sampling: clusters of equal sizes -- Single-stage cluster sampling: clusters of unequal sizes -- Subsampling with units of equal size -- Subsampling with units of unequal size -- Double sampling -- Sources of error in Surveys
Includes references and index.
Keywords: Sampling; Sampling theory